2020
DOI: 10.1177/0883073820953010
|View full text |Cite
|
Sign up to set email alerts
|

Resident Training in Transitioning Youth With Epilepsy Into Adult Care

Abstract: Objective: To appraise the current training of Neurology (N), Pediatric (P), and Med-Peds (MP) residents at MedStar Georgetown University Hospital (MGUH) in providing care to patients with epilepsy who are transitioning from pediatric to adult care. Methods: Through an online questionnaire, we surveyed Neurology, Pediatric, and Med-Peds residents to assess their knowledge, confidence, and experience at transitioning youth with epilepsy to adult-oriented health care. Results: N, P, and MP residents generally ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A significant finding was that adult health providers reported low-levels of confidence in dealing with complex forms of childhoodonset epilepsy. This finding was supported by Tirol and Kumar [20] whose qualitative study of resident doctors found most respondents rated their transition knowledge as very minimal. Respondents reported a lack of exposure to transition processes and the need for improved training.…”
Section: Published Work Acknowledges This Complex Time Withmentioning
confidence: 60%
See 2 more Smart Citations
“…A significant finding was that adult health providers reported low-levels of confidence in dealing with complex forms of childhoodonset epilepsy. This finding was supported by Tirol and Kumar [20] whose qualitative study of resident doctors found most respondents rated their transition knowledge as very minimal. Respondents reported a lack of exposure to transition processes and the need for improved training.…”
Section: Published Work Acknowledges This Complex Time Withmentioning
confidence: 60%
“…This finding was supported in a qualitative study of resident doctors that found most respondents rated their transition knowledge as very minimal [20]. Respondents reported a lack of exposure to transition processes and the need for improved training.…”
Section: Health Services and Systemsmentioning
confidence: 71%
See 1 more Smart Citation